The Relationship between Family Functions and the APGAR Method on the Quality of Life of the Elderly - Rasniah Sarumi; Muhammad Khidri Alwy; Arman (Universitas Mandala Waluya, 2021)
The problem faced by the elderly is the natural aging process. Aging process causes many problems both physical, psychological, social relationship and environment. It has resulted disruption to always need the help, elderly people do not feel qualified because they always felt dependence on others. The existence of a family can support the daily activities of the elderly to be of higher quality.The aim of the study is determinant the relationship between family function toward the elderly life quality in the working place of Puskesmas Waara Muna’s Regency. Type of the study is quantitative by using Cross-Sectional Study approach. There are 71 elderly as sample. Data analysis are Univariate, Bivariate and Multivariate. The results showed that there was a relationship between adaptation (p-value=0,001), partnership (p-value= 0,000), affection (p value=0,040), resolve (p value=0,001) and the quality of life of the elderly. Meanwhile, the growth variable (p value=0,052) has nothing to do with the quality of life of the elderly. The partnership variable has a significant relationship with the quality of life of the elderly (ρ-value<0,05) with a sig. of 0,000 on the quality of life of the elderly. It is recommended for puskesmas to improve health services for the elderly by conducting home visits to carry out direct monitoring of the elderly.